2020
DOI: 10.1177/0956797619894205
|View full text |Cite
|
Sign up to set email alerts
|

Children Delay Gratification for Cooperative Ends

Abstract: To cooperate effectively, both in small-scale interactions and large-scale collective-action problems, people frequently have to delay gratification (i.e., resist short-term temptations in favor of joint long-term goals). Although delay-of-gratification skills are commonly considered critical in children’s social-cognitive development, they have rarely been studied in the context of cooperative decision-making. In the current study, we therefore presented pairs of children ( N = 207 individuals) with a modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 42 publications
1
24
1
Order By: Relevance
“…Similar patterns have been observed in adults (Curry et al, 2008;Harris & Madden, 2002; though see Barclay & Barker, 2020;Wu et al, 2017), as well as in blue jays who are prevented from consuming rewards immediately (Stephens et al, 2002). Children are also better at delaying gratification in cooperative tasks than solo tasks (Koomen et al, 2020). A direct link between delay of gratification and reputational management has been suggested in 3-and 4-year-old children (Ma et al, 2020), although other work has shown that people are unable to anticipate the delayed indirect benefits from their own cooperative investments (Wu et al, 2016).…”
Section: Delay Of Gratificationsupporting
confidence: 70%
“…Similar patterns have been observed in adults (Curry et al, 2008;Harris & Madden, 2002; though see Barclay & Barker, 2020;Wu et al, 2017), as well as in blue jays who are prevented from consuming rewards immediately (Stephens et al, 2002). Children are also better at delaying gratification in cooperative tasks than solo tasks (Koomen et al, 2020). A direct link between delay of gratification and reputational management has been suggested in 3-and 4-year-old children (Ma et al, 2020), although other work has shown that people are unable to anticipate the delayed indirect benefits from their own cooperative investments (Wu et al, 2016).…”
Section: Delay Of Gratificationsupporting
confidence: 70%
“…Only a limited number of studies looked at how delay of grati cation is related to children's prosocial sharing. A positive relationship between delay of grati cation and reciprocal sharing was reported by Moore & Macgillivray (24) and Koomen et al (25) in a modi ed delay of grati cation task in which children could wait to provide bene ts to a familiar third party and by Sebastián-Enesco & Warneken (26) where resources obtained in a delay of grati cation task could be shared with a puppet. To our knowledge, no study has yet measured delay of grati cation and prosocial sharing using two independent tasks where decisions regarding delay are independent from sharing decisions, and involving "real" same-age children as partners testing in a realistic environment (i.e.…”
Section: Introductionmentioning
confidence: 65%
“…Students help each other to learn, share ideas and resources. Thus, the best way to educate in solidarity is practising it through cooperation (Koomen et al, 2020). The same holds true with the factors of solidarity and coexistence, with the research by authors such as Markham (2019) and Valero et al (2018) showing a strong interaction between the two.…”
Section: Discussionmentioning
confidence: 84%